Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Jay had 6 times as much money as Kay. Then Jay gave Kay $33. Jay now has twice as much money as Kay. How much did they each start with?

Sagot :

Answer:

Jay started with $148.5 and Kay with $24.75.

Step-by-step explanation:

With the information provided you know that Jay had 6 times as much money as Kay wich can be expressed as:

J=6K, where

J is the money Jay had

K is the money Kay had

Also, you know that  Jay gave Kay $33 and Jay now has twice as much money as Kay, which would be:

J-33=2(K+33)

Now, you can replace J=6K in this equation and solve for K:

6K-33=2K+66

6K-2K=66+33

4K=66

K=24.75

Then, you can replace the value of K in J=6K:

J=6*24.75

J=148.5

According to this, the answer is that Jay started with $148.5 and Kay with $24.75.